PENGEMBANGAN INSTRUMEN DIAGNOSIS KESULITAN BELAJAR PADA PEMBELAJARAN KIMIA DI SMA - Yamtinah, Sri; Budiyono, Budiyono (Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
Tujuan penelitian ini untuk: (1) mengembangkan instrumen ordered multiple-choice untuk diagnosis kesulitan belajar Stoikiometri kelas X, (2) menetapkan karakteristik dari instrumen, dan (3) membuat profil diagnostik peserta didik sebagai laporan yang informatif. Penelitian pengembangan ini menggunakan model Borg & Gall. Preliminary study menghasilkan pokok bahasan tersulit Stoikiometri. Penetapan atribut dan hierarki atribut dengan focus group discussion dilanjutkan dua putaran teknik Delphi. Indikator dan rumusan butir soal ditelaah expert untuk membuktikan validasi isi dengan rumus Aiken. Ujicoba terbatas dan ujicoba menengah pada sekolah kategori tinggi, sedang dan rendah. Ujicoba kelayakan dilakukan pada sekolah-sekolah di wilayah Surakarta, Karanganyar, Boyolali, dan Sragen. Kesimpulan: (1) penelitian berhasil mengembangkan tiga paket soal Ordered Multiple Choice (OMC) untuk mendeteksi kesulitan belajar peserta didik pada materi Stoikiometri kelas X; (2) butir-butir soal OMC pada paket A, B, dan C memiliki validitas konstruk yang baik dengan Goodness of Fit(GoF) berdasar Smart PLS > 0,36 yaitu 0,437; 0,466 dan 0,433. Instrumen memiliki reliabilitas tinggi berturut-turut 0,79; 0,81 dan 0,75; (3) profil peserta didik berupa laporan diagnostik tentang atribut yang sudah dikuasai dan belum dikuasai peserta didik. Kata kunci: Attribute Hierarchy Method, Ordered Multiple Choice, Graded Response Model ______________________________________________________________ DEVELOPING A DIAGNOSTIC INSTRUMENT FOR LEARNING DIFFICULTIES IN CHEMISTRY IN SECONDARY HIGH SCHOOL Abstract The purposes of this study are to: (1) develop Ordered Multiple Choice (OMC) instruments with a model of Attribute Hierarchy Method (AHM) for the diagnosis of stoichiometry learning difficulties in chemistry learning in secondary high school, (2) determine the characteristic of instruments which have been developed based on the Graded Response Model (GRM), (3) create a diagnostic profile of learners as an informative report. This development research used the Borg & Gall model. The development of the instrument is done using the AHM with the form of OMC. The determination of attributes and attribute hierarchy was done by the focus group discussion (FGD) by three experts, six teachers, and two measurement experts and continued with the Delphi technique by three experts with two rounds. A limited try out was conducted in the high, medium, and low category schools. A feasibility try out was conducted to the high, medium, and low category schools in the regions of Surakarta, Karanganyar, Boyolali, and Sragen. The results are as follows. 1). This research has developed three packages of OMC to detect the learning difficulties of students in the subjects of Chemistry, especially in Stoichiometry of class X. 2). The OMC test items on packages A, B, and C have good construct validity with the Goodness of Fit (GoF) greater than 0.36 namely 0.437, 0.466, and 0.433. 3). The learners' profiles are created in the form of diagnostic report about the attributes which have been mastered and have not been mastered by the learners. Keywords: Attribute Hierarchy Method, Ordered Multiple Choice, Graded Response Model